EFFECT OF MYCORRHIZAL DOSE AND NPK PHONSKA 15-15-15 FERTILIZER ON GROWTH AND YIELD OF PURPLE CORN (Zea mays ceratina Kulesh) - Hilda Yanti Br Torus Pane; Syafrizal Hasibuan; Lokot Ridwan Batubara (Universitas Asahan, 2018)
The research was conducted in the Tanjung Alam village, Sei Dadap Sub-district, AsahanRegency, North Sumatera with flat topography with height of ± 20 m above the sea level, Theresearch was conducted on February 09, 2018 to April 17, 2018. This research was arrangedbased on Factorial Randomized Block Design with 2 treatment factors and 4 replications. Thefirst factor is the dosage of mycorrhiza with 2 levels ie: M0 = 0 g / plot, M1 = 15 g / plot. Thesecond factor was the application of fertilizer PHONSKA NPK 15-15-15, with 3 levels ie P1 = 600 g / plot, P2 = 450 g / plot, and P3 = 300 g / plot. The results of dosage of mycorrhizal dose showed a significant effect on the height 2 weeks after planting number of leaves aged 4 weeks after planting, with the best mycorrhizal dosage at 15 g/plot. application of PHONSKA NPK 15-15-15 fertilizer showed a significant effect on the growth of purple corn at leaf number 6 weeks after planting, with the best treatment at dose of 600 g/plot.The interaction between dosage of mycorrhizal doses and PHONSKA NPK 15-15-15 fertilizer on the growth and production of purple corn plant have a significant effect on plant height 4 and 6 weeks after planting and at the time of flowering.